Early insulin therapy Coordination Council - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2012)
Coordination Council has denoted the importance of adherence to Russian and international guidelines and prominent role of insulin therapy in management of type 2 diabetes mellitus (T2DM). Insulin therapy in T2DM preserves endogenous insulin secretion, prevents or decelerates development of microvascular complications and is known to be the most effective glucose-lowering treatment.